2021
DOI: 10.3389/fphar.2021.659954
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Components and Pharmacological Effects of Mountain-Cultivated Ginseng and Garden Ginseng Based on the Integrative Pharmacology Strategy

Abstract: Panax ginseng C. A. Mey (PGCAM) is a herbaceous perennial belonging to the Araliaceae family, mainly including Mountain-Cultivated Ginseng (MCG) and Garden Ginseng (GG) on the market. We aimed to establish a rapid, accurate and effective method to distinguish 15-year-old MCG and GG using ultra-performance liquid chromatography-quadrupole time-of-flight-tandem mass spectrometry (UPLC-QTOF-MS/MS), and also explored the pharmacological mechanisms of the main components using the Integrative Pharmacology-based Net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…This finding demonstrated the improved efficiency of age differentiation and increased the possibility of identifying key metabolites. In addition to these findings, several studies have indicated that metabolomics can distinguish the metabolic differences of ginseng berries at different ages or maturation stages (Li, Wang, Yang, et al, 2021;Park et al, 2019). The metabolites of ginseng berry continued to change until the fifth ripening stage, and the 3-year-old berries had a higher content of valine, glutamic acid, and tryptophan but a lower content of lactic acid and galactose than 4-year-old berries at the fully ripened stage; additionally, the metabolic pathways affected by different ages involved amino acid metabolism pathways.…”
Section: Age Discriminationmentioning
confidence: 91%
“…This finding demonstrated the improved efficiency of age differentiation and increased the possibility of identifying key metabolites. In addition to these findings, several studies have indicated that metabolomics can distinguish the metabolic differences of ginseng berries at different ages or maturation stages (Li, Wang, Yang, et al, 2021;Park et al, 2019). The metabolites of ginseng berry continued to change until the fifth ripening stage, and the 3-year-old berries had a higher content of valine, glutamic acid, and tryptophan but a lower content of lactic acid and galactose than 4-year-old berries at the fully ripened stage; additionally, the metabolic pathways affected by different ages involved amino acid metabolism pathways.…”
Section: Age Discriminationmentioning
confidence: 91%
“…Modern pharmacological studies have also proven that ginseng has various pharmacological effects, such as immunity-enhancing [ 3 ], anti-aging [ 4 ], anti-fatigue [ 5 ] and anti-tumor effects [ 6 ]. In China, due to excessive foraging and the lack of wild ginseng resources, in order to meet the market demand, people began to study the artificial cultivation of ginseng, commonly known as garden ginseng [ 7 , 8 ]. There are two main ways to cultivate garden ginseng: one way is to cultivate ginseng on land after deforestation, which we call “cutting forest ginseng”, and the other is to cultivate ginseng on farmland, which we call “farmland ginseng”.…”
Section: Introductionmentioning
confidence: 99%
“…Mey) has been used for the treatment of various ailments for the past 2000 years and is considered the “king of herbs” ( Chopra et al, 2021 ). Based on the growth environment and cultivation methods, ginseng has been divided into three types: mountain wild ginseng, mountain-cultivated ginseng (MCG), and garden ginseng (GG) ( Xu et al, 2016 ; Kim et al, 2018 ; Li et al, 2021 ). MCG is grown in natural environments, especially in high-altitude mountains, before being used as a medicine ( Tu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%